Social Networking: Revitalizing Adult Education as a Field of Social Practice - Joyce S. McKnight (Adult Education Research Conference, 2010)
For many years it has been my dream to discover ways to create and sustain online social networks using twenty-first century tools to provide the inspiration and on-going mutual support that twentieth century social activists and community educators found by physically journeying to Highlander. At the 2009 AERC I shared this idea with adult education colleagues in an interactive session in which we identified key characteristics of the Highlander experience including the development of supportive friendships, reflection on practice, creative strategies that could be adapted to particular settings, and the buoyancy of being part of a social movement. I went home more determined than ever to find ways to make the dream a reality. In some ways, this paper is a report to fellow adult educators on progress toward these goals over the past year. The interactive session at the 2010 conference will allow for reflection on the several new developments and their implications for adult education as a field of social practice.